The application of slapping technique and embellishment of power by Marcus Miller / Muhammad Raziq Abd Wahab and Nik Ahmad Shaufiq Nik Iskandar Ariffin - Abd Wahab, Muhammad Raziq; Nik Iskandar Ariffin, Nik Ahmad Shauqi (2020)
Double thumbing, thumb muting, and pop muting techniques are the embellishments for Slapping technique in modern bass playing. A lot of bass players nowadays use this technique for the bass. These techniques are mostly used in Funk and Fusion songs. A composer named Marcus Miller managed to emulate the Slapping techniques and embellishment in his composition. There are several of his works that have slapping techniques that is included in his composition. For this study, the author selected one of Marcus’s composition entitled, ‘Power’. There are several slapping and embellishment techniques in this piece. The main purpose of this study is to identify the application of Slapping technique and embellishment of “ Power” by Marcus Miller. This study suggests that several objectives to investigate the challenges of applying slapping techniques on bass guitar and to find out the approach to practice the slapping technique and embellishment of “power” by Marcus Miller. The author did several interviews to get the finding of the study. The interview was conducted among one bass guitar lecturers, and three bass guitar students, in the Faculty of Music, UiTM Shah Alam. The author used a smartphone to record the conversation during the interview sessions. The author used Google Meet application and recorded it by using the voice recorder application that has been installed on the phone and laptop. The author also analyzes the ‘Power’ score to investigate the slapping techniques and embellishment in the piece. The most primary result shows that the application of techniques use on these pieces was slightly the same for most of the bass player. The application of techniques for this piece is attacking the string with thumb pull and muting the string with right or left finger, most of the participant also adds embellishment which is referred to as a “ghost note’ in playing this piece.